Acupuncture and constraint-induced movement therapy for a patient with chronic stroke: One-year follow-up case report. Issue 46 (November 2017) - Jin, Yuanyuan; Jin, Xiaoqing; Chen, Yidan; Zhu, Jianfang
Abstract: Rationale: Spasticity is a widespread problem in chronic stroke. To date, no study has reported the long-term (up to 1 year) outcomes of acupuncture in combination with constraint-induced movement therapy in patients with chronic stroke. This report describes the successful addition of acupuncture on spasticity and arm function in a patient with chronic stroke and arm paresis. Patient concerns: At screening, the patient was unable to voluntarily extend her interphalangeal or metacarpophalangeal joints beyond the 10 degrees required for constraint-induced movement therapy. However, the BTX type A injection couldn't be used as she had ever suffered a severe allergic reaction in the injection of BTX type A for facial anti-wrinkle. Diagnoses: A 40-year-old female experienced arm paresis after an infarction in the right posterior limb of the internal capsule 2 years before the intervention. Interventions: The BTX type A injection couldn't be used as she had ever suffered a severe allergic reaction in the injection of BTX type A for facial anti-wrinkle, so the patient received 1 hour of acupuncture as an alternative therapy before 5 hours of constraint-induced movement therapy for 12 weekdays. Outcomes: All outcome measures (Modified Ashworth Scale, Fugl-Meyer Assessment, Action Research Arm Test, Motor Activity Log) substantially improved over the 1-year period. Moreover, during the observation period, the patient's muscle tone and arm function did not worsen. Lessons: As a result of a reduction in spasticity, a reduction of learned nonuse behaviors, or use-dependent plasticity after the combined therapy, the arm functions include volitional movements and coordination or speed of movements in the paretic arm have been improved. However, we can not rule out the possibility of an influence of the passage of time or the Hawthorne effect. The costs of the treatment of stroke may be reduced, if this combined therapy proved useful in future controlled studies.